Evaluating Inclusive Education Implementation Using the CIPP Model: A Case Study of SDN Gendongan 01 Salatiga, Indonesia - Khamidah, Shofiya; Sanoto, Herry (Papanda Publisher, 2025)
This study aims to evaluate the implementation of the inclusive education program at SD Negeri Gendongan 01 Salatiga using the CIPP model (Context, Input, Process, Product) in relation to the stages of school management. The research employed an evaluative method with a qualitative descriptive approach. Data were collected through interviews, observations, and document analysis involving the principal, classroom teachers, special education support teachers (GPK), and shadow teachers. The findings indicate that SD Negeri Gendongan 01 Salatiga demonstrates a strong commitment to inclusive education, as reflected in its school vision and focus on the development of students with special needs. However, there are challenges related to facilities and infrastructure, including the absence of dedicated classrooms for students with special needs. The input dimension also revealed limitations in human resources, although the presence of GPK and shadow teachers supports the inclusive program. In terms of process, student support is provided through a structured system, although the effectiveness of facilities and infrastructure still requires improvement. The product evaluation shows positive academic development, albeit with variability in individual student achievement. This study concludes that although the inclusive education program at SD Negeri Gendongan 01 has produced promising results, significant challenges remain that must be addressed to improve the quality of inclusive education. The implications of this study suggest the need to strengthen formal policies and enhance the quality of human resources in inclusive schools.